Microsatellite Genotyping Clarified Conspicuous Accumulation of Candida parapsilosis at a Cardiothoracic Surgery Intensive Care Unit - Magda Diab‐Elschahawi; Christina Forstner; Ferry Hagen; Jacques F. Meis; Andrea Lassnig; Elisabeth Presterl; Corné H. W. Klaassen (2012)
Candida parapsilosis has become a significant cause of invasive fungal infections in seriously ill patients. Nosocomial outbreaks through direct and indirect contact have been described. The aim of this study was the molecular characterization of what appeared to be an ongoing C. parapsilosis outbreak at the cardiothoracic intensive care unit of the University Hospital of Vienna between January 2007 and December 2008. Using two different molecular typing methods-automated repetitive sequence-based PCR (DiversiLab; bioMérieux) and microsatellite genotyping-we investigated the genetic relationship of 99 C. parapsilosis isolates. Eighty-three isolates originated from the cardiothoracic intensive care unit, while 16 isolates were random control isolates from other intensive care units and a different Austrian hospital. The 99 C. parapsilosis isolates analyzed by repetitive-element PCR all showed identical genotypes, suggesting an ongoing outbreak. In contrast, microsatellite genotyping showed a total of 56 different genotypes. Two major genotypes were observed in 10 and 15 isolates, respectively, whereas another 13 genotypes were observed in 2 to 4 isolates each. Forty-one genotypes were observed only once. Closely related genotypes that differed in only a single microsatellite marker were grouped into clonal complexes. When it comes to C. parapsilosis, microsatellite genotyping is a more discriminative method than repetitive-element PCR genotyping to investigate outbreaks.